THE PROGNOSTIC AND PREDICTIVE VALUE OF KI-67 PROLIFERATION INDEX AND uPA/PAI-1 COMPLEX IN SERUM FOR PATIENTS WITH EARLY INVASIVE BREAST CANCER - Pušina, Sadat; Hodžić, Edin; Salibašić, Mirhan; Bičakčić, Emir; Herenda-Pušina, Naida; Halilović, Emsad (Sanamed, 2024)
Introduction: Breast cancer, the most common malignancy in women, represents a significant health issue, and biomarkers such as the Ki-67 index and uPA/PAI-1 complex can provide insight into treatment outcomes and therapeutic response.Objective: The primary outcome of the study was the assessment of 5-year disease-free survival (DFS), defined as the postoperative period until the occurrence of loco-regional or distant metastases and death from any cause.Patients and Methods: A retrospective cohort study included 166 patients with early invasive breast cancer, in whom the prognostic and predictive significance of the uPA/PAI-1 complex and Ki-67 biomarkers in surgically treated patients at the Clinic for General and Abdominal Surgery of the University Clinical Center in Sarajevo was evaluated during the period from September 2015 to February 2017.Results: Univariate regression analysis identified an increased probability of DFS shorter than five years in patients with negative hormone receptors, positive HER-2 receptor, ≥8 positively mph nodes, and a Ki-67 index ≥14% (p
Keywords: biomarkers; general surgery; treatment outcome; women's health